Mixed-mode ventilation in Malaysia' shopping malls: a taxonomy study - Idowu, Ibiyeye Aminat; Jaafar, Mohamad Fakri Zaky; Shari, Zalina; Dahlan, Nur Dalilah (Faculty of Design & Architecture, Universiti Putra Malaysia, 2015)
The quest for building sustainability and reduction in building energy consumption has called for alternative means to cooling in buildings. Natural ventilation has been considered in this regard. However, due to its limitations, buildings are now shifting towards mixed-mode ventilation, which is a combination of the best features in natural and mechanical ventilation also offering huge advantages for reducing energy consumption. This shift will be a gratifying advantage in retail buildings since retail buildings account for the largest energy consumption in the commercial sector in Malaysia. Unfortunately, in Malaysia, mixed-mode ventilation has not been largely employed in retail buildings, particularly shopping malls. Furthermore, little information is available on malls with mixed-mode ventilation. Therefore, this study aims to explore and classify different application modes of mixed-mode ventilation strategy adopted in Malaysia’s existing malls. Relevant literature was reviewed and site visitations and observations were conducted. Out of 105 malls identified in Selangor, Kuala Lumpur and Putrajaya, only six included passive strategies in their ventilation approach. These malls were identified as operating under mixed-mode ventilation and were further grouped under different categories of mixed-mode ventilation strategy. This taxonomy study provides the basis for classifying mixed-mode ventilation in retail buildings and will potentially create awareness among designers and building owners on the growing effort of improving and encouraging energy efficiency in the commercial building sector.